KEPUTUSAN KONSUMEN PADA KOMUNITAS ORGANIK DALAM MELAKUKAN PEMBELIAN BERAS ORGANIK DI KOTA BANDUNG (Studi Kasus di Komunitas 1000 Kebun) - Nurarifah, Farah; Sukayat, Yayat (Universitas Galuh, 2023)
1000 Kebun Community is an organic community based in Bandung that aims to live a healthy life and care for the environment. The identity that is built on community members may not always be the main thing because many considerations are made by consumers when going through the purchasing decision process. This study aims to identify which community members consume organic rice and describe the consumer decision process in the organic community in purchasing organic rice in the city of Bandung. The method in this study uses qualitative analysis. The results showed that organic rice consumers were dominated by women aged 17-25 years, had a master's degree, worked as students, had one family member, and were in the income group of more than IDR 6,000,000 per month. The purchase decision process is carried out through five stages, namely, (1) recognition of needs based on self-actualization motivation and a sense of security, and (2) information search, carried out by active participants. (3) Evaluation of alternatives, namely considering purchases based on price and organic certification. (4) Participants' purchasing decisions tend to be influenced by the people around them and purchases are made through supermarkets or local organic farmers. (5) Post-purchase evaluation is dominated by satisfaction and driven on health and responsibility grounds to support local organic farmers.